Ab Initio Study of the Effect of Sulphur Concentration on the Structural, Electronic and Optical Properties of CuIn(Se1-xSx)2 Compound using Generalized Gradient Approximation - Merabet, Moussa; Bouchama, Idris; Chihi, Tayeb; Foudia, Lamis; Saidi, Faycal; Bouarissa, Nadir (Engineering, Technology & Applied Science Research, 2025)
CuInSe2 (CIS) is a very promising material for thin film solar cells due to its unique optoelectronic properties. Sulfur (S) loading has been examined as an improvement to its performance. In this study, Density Functional Theory (DFT) calculations were used to evaluate the effect of S doping on the structural, electrical, and optical properties of CuIn (Se1-xSx)2. The results show that S doping causes significant changes in the band structure and defect formation energy. The results obtained provide important insights into the potential of S-doped CIS as a high efficiency material for the fabrication of optoelectronic and photovoltaic devices.